Dinamismo ecológico y evolución cultural en nuestras montañas - Montserrat Recoder, Pedro (Geographicalia, 2016)
Some ideas on mountain profiting resources, based in the natural, ecological dynamism, are developed in this paper; plants and grazing animals in mountains, along millions of years, are mutually adapted to heavy grazing. Human cultures, with grazing animals, also explain human adaptations to profit and maintain a very nice mountain landscapes. Gregarism in animals and men was essential, but now the land use evolues and few or alien animals come to the mountains. The city men profit other resources in mountains and the landscape is changing. The development sustainable must be changed to a sustained internal gestion under a more easy human action.